A Robust Control of D-STATCOM for Voltage Stability - Midhuna, A.; Baskaran, K. (Journal of ISMAC, 2022)
Power Quality enhancement is a major topic among researchers as the usage of non-linear loads has increased vastly. The purpose of this work is to maintain constant DC link voltage in hybrid energy system which contains Doubly Fed Induction Generator (DFIG) based Wind Energy Conversion System (WECS) and Photovoltaic (PV) system. Among the various available Flexible AC Transmission System (FACTS) devices, Distribution Static Compensator (D-STATCOM) provides better voltage stability with Voltage Source Converter (VSC). LUO converter is used, as it has excellent voltage-gain ratio. The utilization of Adaptive Neuro-Fuzzy Inference System (ANFIS) as Maximum Power Point Tracking (MPPT) assures controlled output and supports the extraction of complete power from the PV panel. This work evaluates the performance of the proposed inverter through MATLAB simulation.